Iran's military interventions patterns, drivers, and signposts - Tabatabai, Ariane M.; Chandler, Nathan 1982-; Frederick, Bryan; Kavanagh, Jennifer 1981- (RAND Corporation, 2021)
In recent years, Iran has risen as one of the most significant regional challenges faced by the United States, with Tehran's nuclear and ballistic missile programs, support for terrorist groups and militias, cyber activities and influence operations, and military interventions in the region. In this report, the authors assess when, where, why, and how Iran conducts military interventions and identify key signposts of Iranian military interventions that can be used as early warning indicators for U.S. military planners and that can guide decisions about the use of forces in the Middle East region. They identify the factors that are most likely to shape Iran's military intervention decisions and analyze those factors as they relate to two detailed case studies: (1) Iran's involvement in the ongoing Syrian civil war and (2) Iran's post-2014 intervention in Iraq to counter the Islamic State in Iraq and Syria. The future of great-power competition and how it plays out in the Middle East, coupled with the regional landscape, are important factors that will shape how Iran sees its military activities. Although a move away from a period of greater U.S. power in the region would seem to provide fewer threats and more opportunities for Iran, the relations among Beijing, Moscow, and Washington and how they affect Iranian perceptions of the regional balance of power bear careful monitoring
Keywords: Intervention (International law) / Government policy / Iran / Case studies; Iran / Foreign relations; Military assistance, Iranian / Syria; Military assistance, Iranian / Iraq; Syria / History / Civil War, 2011-; IS (Organization); Diplomatic relations; Iran; Case studies